ANALYSIS OF THE RELIABILITY OF ELECTRICAL DISTRIBUTION SYSTEMS USING THE TECHNICAL SECTION METHOD AND RNEA REPEAT GIBP-MESIR - Aprialdi, Rahmat; Aini, Zulfatri (DPTE FT UNY, 2023)
The electricity distribution system can be said to be reliable if the process of delivering electricity to the customer does not experience significant interruptions. In the PT. PLN (Persero) ULP Duri found a variety of disturbances in one year. The resulting impact is, energy that is not channeled during the occurrence of disruption, thus making the reliability value on the electricity distribution system unreliable. The study aims to analyze the reliability of the system on the GIBP-MESIR repeat, using the Techniqeu Section Method and RNEA Method, as well as calculate the economic losses over a year. System reliability index results using Section Technique Method SAIFI 1,258 times/customer/year, SAIDI 5,324 hours/customer/year and CAIDI 4,232 hours/customer/year. The RNEA method SAIFI 1,844 times/customer/year, SAIDI 7,819 hours/customer/year, and CAIDI 4,239 hours/customer/year. For both methods the SAIFI, SAIDI, and CAIDI values are below SPLN 88-2 1986, then it can be said to be reliable. Economic fulfillment of Section Technique Method with ENS value 59.194.677,96kWh, AENS 3.453,39 kWh/customer, and Rp 85.518.551.248. RNEA method values ENS 86.933.685,93 kWh, AENS 5.071,681 kWh/customer, and Rp. 125.593.096.063 for one year.